Contratos em propriedade intelectual : a utilização nas instituições de ensino superior nordestinas - Moura, Sâmia Passos Barboza (2015)
Intellectual production in higher education institutions is increasing. Every day there is a new technology or study, often with subsidies and private companies incentives. One has to emphasize that this whole process of creation started in these institutions has primarily intended to be reversed, in many ways, in blessings for the whole society. In this way, it deserves huge reflection of the need to protect it produces without losing any outcome that should be considered a public good. Thus, this document was created with the objective of analyzing how the protection of intellectual property in these institutions, specifically whether there are and how they work contracts intellectual property issued by higher education institutions in the northeast axis, with a view to intellectual production occurred the cradle of these institutions. For both data obtained were analyzed both at the sites of the universities themselves as the data obtained through a questionnaire, in addition to intellectual property contracts they use. The post was analyzed all the protection provided for in the Brazilian legislation on the matter, used as a guide. With this, was expected to show that the actual importance on intellectual property protection for these institutions, as well as the whole society.